2006
DOI: 10.1016/j.febslet.2006.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the extrinsic subunit of photosystem II, PsbU, in Synechococcus PCC 7942 results in elevated resistance to oxidative stress

Abstract: PsbU is a subunit of the extrinsic complex attached to the core of photosystem II. A PsbU-mutant of Synechococcus PCC 7942 was isolated based on its elevated resistance to externally applied oxidative stress. PsbU-mutant exhibits fast rates of degradation of the photosystem II core protein, D1, under subsaturating as well as high-light conditions. While forward electron transfer is not affected, back electron flow is severely impaired in the mutant. We suggest that impairment of psbU results in production of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 49 publications
3
35
0
1
Order By: Relevance
“…In the presence of DCMU, the main fluorescence decay component, which reflects the recombination of Q A -with the S 2 state is slower in the mutant (T 3 ~3.4 s) than in the wild type (T 3 ~1.6 s) , which is in agreement with previous data (Balint et al, 2006) (Fig.4.10.B, Table 1). …”
supporting
confidence: 83%
See 4 more Smart Citations
“…In the presence of DCMU, the main fluorescence decay component, which reflects the recombination of Q A -with the S 2 state is slower in the mutant (T 3 ~3.4 s) than in the wild type (T 3 ~1.6 s) , which is in agreement with previous data (Balint et al, 2006) (Fig.4.10.B, Table 1). …”
supporting
confidence: 83%
“…In a study by Balint et al it was reported that the rate of the forward electron transport from Q A -to Q B was not affected by the absence of the PsbU subunit, while the S 2 Q A -charge recombination process is slowed down in Synechococcus 7942 (Balint et al, 2006). However, flash fluorescence data presented in that study were rather noisy, and the different phases of the fluorescence decay could not be clearly resolved.…”
Section: 77k Fluorescence Emission Spectra (Excitation At 600nm) Inmentioning
confidence: 45%
See 3 more Smart Citations